The understanding of tomb sweeping with the perspective of digital art and culture - Yunzhu, Huo; Husain , Dr. Adzira Binti; Jamali, Dr. Siti Salmi (International Journal of Basic and Applied Sciences, 2025)
Family cohesion is crucial, irrespective of the period. Ancestral veneration is an integral aspect of Chinese cultural practices. Although residing in the digital realm, it is nevertheless actively observed. The researchers suggest that this occasion be transitioned from tradition to modernity while yet maintaining the sacredness of the ceremony. This exploratory work aims to understand the Tomb Sweeping mechanism from the perspective of digital art, such as mobile applications, and its cultural impact in China. Besides, it also addresses to the rapid advancement in the technology by focusing on people’s actual experiences by using digital mobile application in terms of Tomb Sweeping, not as a fixed standard against which everything else is judged, the research starting point for identifying the Tomb sweeping cultural terrains on which social preferences are formed and which they can use to influence the ever-changing terms of their own lives. For this reason, there comes a time when several studies came into existence to determine the effects of digital platforms from the perspective of art and culture. Hence, more work may be required concerning to the Tomb-sweeping culture. Therefore, rely on qualitative study that employs in-depth, semi-structured interviews with the two major cemeteries (Jin Rohan Ecology and Baifang) in Mianyang, China. Overall, 12 groundskeepers or sextons were recruited and interviewed. All the interviews will be analyzed thematically. In a society that traditionally avoids making any reference to death, it is useful to reduce cultural taboos and construct positive meanings in the end-of-life. Thus, the current work is exploratory that focusing on understanding the Tomb Sweeping mechanism from the perspective of digital technology, and its cultural impact in China.